Strengthening the Capital Market in India: A Key to Growth - Bajwa, Rubeena (Indian Journal of Finance, 2016)
In order to ensure consistent and inclusive growth of an economy, capital markets play a critical role in mobilizing the savings in productive and long-term assets. Capital markets provide a medium of transforming the economy into a more efficient, competitive market place, provide a medium to diversify the risk, improve the information quality and lead to the adoption of stronger corporate governance norms. The study focused upon the importance of capital markets for sustainable growth in emerging markets like India. The relationship between economy and growth of the capital market in the amount of capital generated through primary issuances, exchange trading turnovers, market indices, market capitalization, and so forth was analyzed.